Dialogicity of Southern People Between Darmee Poetry and Colloquial Language in Hassan Kareem Ati’s Novel “Standing on one Leg - Dr. Zahraa Jasim Kazem (Journal of College of Education, 2026)
This study aims to investigate dialogicity of Southern Iraqi people between the poetry of Darmee and colloquial dialect, The Darmee is described as a type of folkloric poetry which is deeply rooted in the consciousness of Iraqi Southern community, whereas the colloquial language is described as the expressive medium which revitalizes and sustains it. The study hypothesizes that the Darmee is not merely regarded as a lyrical text but as a dialogic speech which reflects the cultural and social dynamics of the southern Iraqi milieu in which the individual voices integrate with the communal ones and aesthetic dimension merges with therapeutic function. The study highlights the analysis of the relationship between Darmee as a structured artistic text , and the southern colloquial as a daily communicative tool. It illustrates how colloquial dialect acquires an aesthetic element when integrated into the Darmee’s structure and how the poetic text gains strength from its intimacy with people’s spoken tongue and imagination. Furthermore, this study explores the functions of dialogic in expressing love and emotions, or critiquing social reality, or documenting cultural traditions. Findings of the study reveal that dialogicity in Darmee generates an interactive space that embodies southern identity, blending art with reality and oral with written forms, thereby preserving the popular memory and reinforcing the continuity of colloquial poetry